The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1080/pdp.21.6.557.567
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Acute Phase Response to Differentiate Between Viral and Bacterial Infections in Children

Abstract: The objective of this study was to document the reduced acute phase response that appears in children with viral as opposed to bacterial infections. The white blood cell count (WBCC), the erythrocyte sedimentation rate (ESR), and leukocyte and erythrocyte adhesiveness/aggregation were determined in 36 children with acute bacterial infection, 29 children with viral infection, and 19 controls. A significant reduced WBCC, ESR, and leukocyte and erythrocyte adhesiveness/aggregation was noted in the children with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Precisely, the review emphasizes measurement of erythrocyte aggregation in vivo in real time continuously using quantitative imaging techniques. Among • Metabolic syndrome (Gyawali and Richards 2014;Gyawali et al 2014b;Justo et al 2003;Toker et al 2005;Vayá et al 2011b) • Inflammatory bowel disease (Maharshak et al 2009;Novacek et al 1996;Zilberman et al 2005) • Atherothrombosis (Assayag et al 2005;Berliner et al 2001Berliner et al , 2005Rogowski et al 2005;Zeltser et al 2004a) • Systemic lupus erythematosus (Santos et al 2011;Spengler et al 2011) • Myocardial infarction, ischemic stroke, coronary syndrome (Ami et al 2001;Kim et al 2013;Lakshmi et al 2011;Lee et al 2008;Sargento et al 2003;Shenhar-Tsarfaty et al 2008) • Obstructive sleep apnea (Peled et al 2008) • Pelvic inflammatory disease (Almog et al 2005) • Exposure to silica and benzopyrine (Duan et al 2016) • Psoriasis (Vayá et al 2013c) • Infection/sepsis (Ami et al 2001;Baskurt et al 1997;Czepiel et al 2014;Rogowski et al 2000;Urbach et al 2002) • Dyslipidemia (Schechner et al 2003) • Gaucher's disease (Zimran et al 2004) • Anemia with heart failure (Wang et al 2013) • Aging (Vayá et al 2013a) • Ischemia reperfusion (Brath et al 2010) • Deep vein thrombosis (Krieger et al 2004) • Population with and without cardiovascular diseases…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precisely, the review emphasizes measurement of erythrocyte aggregation in vivo in real time continuously using quantitative imaging techniques. Among • Metabolic syndrome (Gyawali and Richards 2014;Gyawali et al 2014b;Justo et al 2003;Toker et al 2005;Vayá et al 2011b) • Inflammatory bowel disease (Maharshak et al 2009;Novacek et al 1996;Zilberman et al 2005) • Atherothrombosis (Assayag et al 2005;Berliner et al 2001Berliner et al , 2005Rogowski et al 2005;Zeltser et al 2004a) • Systemic lupus erythematosus (Santos et al 2011;Spengler et al 2011) • Myocardial infarction, ischemic stroke, coronary syndrome (Ami et al 2001;Kim et al 2013;Lakshmi et al 2011;Lee et al 2008;Sargento et al 2003;Shenhar-Tsarfaty et al 2008) • Obstructive sleep apnea (Peled et al 2008) • Pelvic inflammatory disease (Almog et al 2005) • Exposure to silica and benzopyrine (Duan et al 2016) • Psoriasis (Vayá et al 2013c) • Infection/sepsis (Ami et al 2001;Baskurt et al 1997;Czepiel et al 2014;Rogowski et al 2000;Urbach et al 2002) • Dyslipidemia (Schechner et al 2003) • Gaucher's disease (Zimran et al 2004) • Anemia with heart failure (Wang et al 2013) • Aging (Vayá et al 2013a) • Ischemia reperfusion (Brath et al 2010) • Deep vein thrombosis (Krieger et al 2004) • Population with and without cardiovascular diseases…”
Section: Discussionmentioning
confidence: 99%
“…Some studies noted significant reductions in erythrocyte aggregation and improved hemorheological profiles (Allegra et al 1995;Nicolaides 2003) after lowering the inflammatory state through lifestyle modifications (Raz et al 2007;Sandor US assessment of erythrocyte aggregation and inflammation • P. Gyawali et al et al 2014) or by the use of anti-inflammatory therapeutic agents (Ge et al 2016;Jiang and Lian 2015;Kelly and Dominguez 2010;Li et al 2015;Szentkereszty et al 2014). Lastly, some studies (n = 15) underscored erythrocyte aggregation as a superior or independent marker of inflammation (Anuk et al 2002;Assayag et al 2005Assayag et al , 2008Berliner et al 2002Berliner et al , 2005Gyawali et al 2016;Levin et al 2006;Maharshak et al 2002;Rotstein et al 2002a;Sharshun et al 2003;Urbach et al 2002Urbach et al , 2003Urbach et al , 2005Vayá et al 2013b) or sepsis (Yeom et al 2017). Only 1 study reported increased erythrocyte aggregation with aging and associated it with increase in inflammation (Vayá et al 2013a).…”
Section: Description Of Studiesmentioning
confidence: 99%